Changes of tetramethylpyrazine-producing functional microorganisms during stacking fermentation in the 1st (Xiasha) and the 2nd (Zaosha) rounds of sauce-flavor Baijiu production - LONG Yafei, ZHU Zi, GUO Chunqin, RAN Guangyao, HU Zhihui, WU Deguang (Zhongguo niangzao)
Tetramethylpyrazine (TTMP) is an important flavor substance in sauce-flavor (Jiangxiangxing) Baijiu, showing sweet, nutty and floral aromas, which is one of the important health factors of Chinese Baijiu. In this paper, using fermented grains of stacking fermentation in the 1st (Xiasha) and the 2nd (Zaosha) rounds of sauce-flavor Baijiu production as research objects, all microbial genes in the fermented grains samples were sequenced and analyzed by macrowhole gene sequencing technology, and the changes of tetramethylpyrazine-producing functional microorganisms during stacking fermentation in the 1st and the 2nd rounds of sauce-flavor Baijiu production were studied. The results showed that the main tetramethylpyrazine-producing functional microorganisms during the stacking fermentation were Weissella paramesenteroides, Levilactobacillus brevis, Pediococcus pentosaceus, Bacillus sonorensis, Pediococcus acidilactici, Kroppenstedtia eburnea, and Saccharomyces cerevisiae, etc. In the 1st round the functional microorganisms decreased except for P. acidilactici. In the 2nd round, yeast gradually increased, L. brevis was the largest on the 2nd day of stacking fermentation, and other microorganisms accounted for a relatively small proportion.